2011
DOI: 10.1111/j.1365-3040.2011.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of irradiance on the C allocation in the coastal marine diatom Skeletonema marinoi Sarno and Zingone*

Abstract: ABSTRACT. Inorganic carbon acquisition, fixation and allocation, and silicic acid and orthophosphate uptake were also studied. The C : P ratio was below the Redfield ratio, especially at LL. In HL cells, N quota was halved, C quota was similar, silica quota was lower, growth rate and long-term net primary productivity were almost doubled, relative to LL cells. The HL : LL cell quota ratios were 6 for lipid, 0.5 for protein and 0.4 for carbohydrate. Phosphoenolpyruvate carboxylase (PEPc) and glutamine synthetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 76 publications
5
36
1
1
Order By: Relevance
“…Thus, these cells had relatively high NPP compared to the growth rate. Carbon fixation has been proposed to be a way to deal with excess energy (57). The drastic decrease in Fv/Fm, epoxidation state, and Chl a/Chl b ratio for the 0.32-max culture compared to the 0.97-max and the P-replete cultures is in agreement with the necessity to dissipate excess energy for the cells under this treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, these cells had relatively high NPP compared to the growth rate. Carbon fixation has been proposed to be a way to deal with excess energy (57). The drastic decrease in Fv/Fm, epoxidation state, and Chl a/Chl b ratio for the 0.32-max culture compared to the 0.97-max and the P-replete cultures is in agreement with the necessity to dissipate excess energy for the cells under this treatment.…”
Section: Discussionsupporting
confidence: 69%
“…There is evidence that the shift of carbon fluxes from carbohydrate to lipid biosynthesis in microalgae species is possible. The energy demand for the biosynthesis of lipids was much higher than that of carbohydrates (lipid has a much higher energy value, about 2.25 times), therefore lipids could serve as an effective energy and carbon storage providing a larger sink for the available energy, especially when light was in excess to the requirement for growth (Li et al, 2011;Norici et al, 2011;Msanne et al, 2012). Furthermore, the enhanced synthesis of lipid (TAG) can consumed excessive electrons from over-reduced photosynthetic electron transport chain under high light stress.…”
Section: Photosynthetic Carbon Allocation Under Different Light Intenmentioning
confidence: 99%
“…However, those stress generally concomitant with lower biomass productivity and thus low overall lipid productivity (Hu et al, 2008;Ho et al, 2014). Light supply as an environmental factors not only greatly affect algae photosynthesis as well as cell composition and metabolic pathway, but also the economic efficiency of the algae cultivation process (Norici et al, 2011;He et al, 2015), and consequently, the supply and efficient utilization of light energy have been the greatest scientific and technological challenge in http://dx.doi.org/10.1016/j.biortech.2015.05.021 0960-8524/Ó 2015 Elsevier Ltd. All rights reserved. research and development on commercial cultivation of microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids store more energy in smaller molecules, but the processes of lipid synthesis and catabolism are slower compared with carbohydrate metabolism (Lancelot and Mathot, 1985). It has been shown that other factors such as nutrient depletion (Reitan et al, 1994;Breteler et al, 2005) or excess light energy (Norici et al, 2011) may increase cellular lipid content in diatoms. Along with the mapping and identification of protein coding regions of microalgae genomes, genetic engineering is a rapidly developing field that may provide a tool to enhance lipid synthesis and storage in algae for use in biofuel production (Radakovits et al, 2010).…”
mentioning
confidence: 99%